2014
DOI: 10.1051/0004-6361/201322794
|View full text |Cite
|
Sign up to set email alerts
|

Cool carbon stars in the halo and in dwarf galaxies: Hα, colours, and variability

Abstract: The population of cool carbon (C) stars located far from the galactic plane is probably made of debris of small galaxies such as the Sagittarius dwarf spheroidal galaxy (Sgr), which are disrupted by the gravitational field of the Galaxy. We aim to know this population better through spectroscopy, 2MASS photometric colours, and variability data. When possible, we compared the halo results to C star populations in the Fornax dwarf spheroidal galaxy, Sgr, and the solar neighbourhood. We first present a few new di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Our primary source, providing just over half of all our variable carbon stars, comes from the lists published by the Mauron group (Mauron et al 2004;Mauron, Kendall, & Gigoyan 2005;Mauron, Gigoyan, & Kendall 2007b;Mauron 2008;Mauron et al 2014). These were selected from candidates based on 2MASS (Skrutskie et al 2006) photometry and then spectroscopically confirmed.…”
Section: Mauron Et Al Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Our primary source, providing just over half of all our variable carbon stars, comes from the lists published by the Mauron group (Mauron et al 2004;Mauron, Kendall, & Gigoyan 2005;Mauron, Gigoyan, & Kendall 2007b;Mauron 2008;Mauron et al 2014). These were selected from candidates based on 2MASS (Skrutskie et al 2006) photometry and then spectroscopically confirmed.…”
Section: Mauron Et Al Samplementioning
confidence: 99%
“…There may be artefacts in the period determination for both Mauron et al (2014) and ourselves, due to the cadence of the Catalina observations that we both use, so it is also valuable to compare our periods to other data sets. A few stars are also shared between our first sample and that of Battinelli & Demers (2012, 2013, and allow us to compare the periods determined.…”
Section: Period Determinationmentioning
confidence: 99%
“…The observed K and J magnitudes are available only at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/568/A100 distribution with those of similar variables of other stellar populations. Recently Mauron et al (2014) have determined periods for a much larger sample of halo C stars. They find that the period distribution of the halo Miras matches rather well a similar distribution for the Sgr Miras observed by Battinelli & Demers (2013), thus suggesting a probable common origin.…”
Section: Introductionmentioning
confidence: 99%
“…Since most of our new program stars now have periods determined by Mauron et al (2014), we prefer here to discuss the fraction of Miras among C stars and investigate their NIR colors.…”
Section: Introductionmentioning
confidence: 99%
“…Bessel & Brett 1988;Leggett et al 2002;Cruz et al 2003). We show the results in Figure 4 together with those of confirmed carbon stars from FBS and other dataset (Alksnis et al 2001;Mauron 2008;Mauron et al 2014). The positions of V381 Lac corresponding to the dates reported in Table 2 are indicated by the numbers in black.…”
Section: Infrared Diagramsmentioning
confidence: 97%